Fighting Against the Fate in John Green’s The Fault in Our Stars (Kaladarpan कलादर्पण, 2023)
The paper is about the existential battle of Hazel Grace Lancaster and Augustus in John Green’s The Fault in Our Stars. They show their optimistic behavior against pessimistic situation. There is the feeling of confidence and sense of optimism in the characters against the dark situation of their lives. The main focus of this study is to explore how the characters in the novel embrace sense of optimism despite their terminal illness. In doing so this paper applies, Jean Paul Sartre’s theory of existentialism as the tool of analyses. It mainly revolves around how Hazel chooses life than death despite adverse situation to assert her existence illness.